Do Girls Really Outperform Boys in Educational Outcomes? - Perihan Ozge Saygin (University of Mannheim, Department of Economics, 2014)
The reversing achievement gap across genders observed in many countries has led to a heated debate on the persistent gap in academia and other top fields. Using Turkish administrative data and the particular institutional characteristics, this pa- per aims to analyze the gender gap in educational outcomes from different methods of evaluation and the gender gap in college applications. The results contribute to the discussion of the gender gap in performance in education suggesting that evaluation systems might have gender biased impacts on students and the under- representation of females in top fields can not be explained by differences in test scores.
urn:nbn:de:bsz:180-madoc-355113
Keywords: 330; gender gap; test scores; university entrance exam